DAYA BUNUH LARUTAN TANAMAN DAUN SALAM (SYZYGIUM POLYANTHUM) TERHADAP KEMATIAN LARVA AEDES SP. - Herliya Fatimah; Isnawati .; Tien Zubaidah (GEMA LINGKUNGAN KESEHATAN, 2022)
Dengue Hemorrhagic Fever (DHF) is increasing every day so it is necessary to control efforts, namely by killing larvae using bay leaf plants (Syzygium polyanthum). The purpose of this study was to determine the effectiveness of the larvicidal solution of bay leaf in controlling larvae of Aedes sp. This research uses the true experiment method with Post Test Only Group Design. The concentration variations used were 0%, 15%, 20%, 25%, 30% and 35% in 100 mL of water with 4 repetitions. The population and samples used were Aedes aegypti and Aedes albopictus instar III larvae, each containing 600 larvae containing 25 larvae in each container. The results showed that the LC50 of bay leaf solution within 24 hours had the largest number of Aedes aegypti and Aedes albopictus larvae mortality at a concentration of 35% with 100% mortality. The results of the Anova Two Way test obtained a sig value. 0.000 ɑ (0.05), meaning that there is an influence on the yield of dead larvae based on variations in concentration. It was concluded that each concentration of bay leaf solution could kill a different percentage of larvae. Suggestions for further researchers to determine the concentration variation of bay leaf larvicide solution which is more effective in killing Aedes sp.